From the immune system to mood disorders especially induced by Toxoplasma gondii: CD4+ T cell as a bridge - Wang, Qing; Zhong, Yue; Chen, Nannan; Chen, Jinling (Frontiers in Cellular and Infection Microbiology, 2023)
Toxoplasma gondii (T. gondii), a ubiquitous and obligatory intracellular protozoa, not only alters peripheral immune status, but crosses the blood-brain barrier to trigger brain parenchymal injury and central neuroinflammation to establish latent cerebral infection in humans and other vertebrates. Recent findings underscore the strong correlation between alterations in the peripheral and central immune environment and mood disorders. Th17 and Th1 cells are important pro-inflammatory cells that can drive the pathology of mood disorders by promoting neuroinflammation. As opposed to Th17 and Th1, regulatory T cells have inhibitory inflammatory and neuroprotective functions that can ameliorate mood disorders. T. gondii induces neuroinflammation, which can be mediated by CD4+ T cells (such as Tregs, Th17, Th1, and Th2). Though the pathophysiology and treatment of mood disorder have been currently studied, emerging evidence points to unique role of CD4+ T cells in mood disorder, especially those caused by T. gondii infection. In this review, we explore some recent studies that extend our understanding of the relationship between mood disorders and T. gondii.